New Trends In The Interpretation Of The Poetry Of Vasko Popa Vertical Land And Serbianbyzantine Heritage - Seatović, Svetlana (Slavica Lodziensia, 2017)
This paper presents fi ndings on the interpretation of the poetry of Vasko Popa in the last 25 years. They point to a shift in the analyzes that follow new theoretical insights. In the case of collections Vertical land shows how the medieval Serbian and Byzantine heritage built into the cycle of poems in the collection, with special emphasis on the cycle of „Pilgrimage”.